Exploring the Efficacy of Music Therapy in Alleviating Depressive Symptoms among Young Adults: A Randomized Controlled Trial - Anewa Kahewa; Christin Anastasya (Acta Psychologia, 2023)
This research investigates the efficacy of music therapy in reducing depressive symptoms among young adults, offering a comprehensive exploration of both quantitative and qualitative dimensions. Employing a randomized controlled trial (RCT) design, participants aged 18 to 25 were randomly assigned to either a music therapy intervention group or a control group. Quantitative analyses, including t-tests and ANOVA, revealed a statistically significant reduction in depressive symptoms among the music therapy group. Qualitative insights highlighted themes of emotional expression, increased self-awareness, and a sense of connection. The findings underscore the therapeutic potential of music therapy, aligning with and enriching existing literature. Implications include the integration of music therapy into mental health programs, personalized interventions for young adults, and future research exploring individual factors and longitudinal effects.